Marketing a Mental Health Specialization: The 4 P’s of Play Therapy - Putulowski, Joe; Crosby, Robert (Technium Social Sciences Journal, 2020)
Nearly half of all healthcare service companies fail within the first four years, negatively affecting the entrepreneur, customer, and the surrounding economy. Additionally, each time a healthcare establishment fails, there is a negative impact on the consumer as much needed healthcare services become unavailable to the community. Lack of effective market strategies and consumer awareness is one of the main reasons that new businesses fail. To address this problem, marketing experts apply the marketing mix, most commonly executed through the 4 P’s of marketing: product, promotion, place, and price. Researchers have begun to apply this marketing framework to the healthcare industry; however, there has been limited application of the 4 P’s to mental health care and the critical specializations that exist within that industry. In the present study, we apply the 4 P’s marketing framework to play therapy, an evidence-based psychotherapy specialization. Drawing from literature, we define the product as a form of counseling in which the therapeutic powers of play are used to resolve psychosocial difficulties in young children. Using a sample of 234 adults attending an online university, we conducted an online survey-based experiment to determine promotion (i.e., where potential clients are most likely to look for therapeutic services), placement (i.e., how much farther clients are willing to drive to see a specialist versus a non-specialist), and price (i.e., how much more clients are willing to pay for a specialist versus a non-specialist). Implications for small mental health business are discussed.